Pengaruh self-efficacy terhadap kemampuan representasi matematis siswa SMP - Septi Zunita Dwi Astuti; Tri Sri Noor Asih; Walid Walid; Zaenuri Zaenuri (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Numerous studies on self-efficacy and students’ mathematical representation skills have been conducted; however, the results remain inconsistent, and thus no general conclusion has been reached regarding a significant relationship between these two variables. Given this situation, this study aims to analyze the effect of self-efficacy on students’ mathematical representation skills at the junior high school level. This study employs a quantitative approach using a survey design. The research subjects were students at State Junior High School 24 in Semarang, selected using purposive sampling; as a result, Class VIII H, consisting of 30 students, was chosen as the research sample. Data collection was conducted using a self-efficacy questionnaire comprising 25 statements and a mathematical representation ability test consisting of three essay-type questions. Statistical analysis results indicate a significant relationship between self-efficacy and mathematical representation skills, classified as a moderate correlation. Furthermore, self-efficacy was found to have a significant positive influence, leading to the conclusion that it is one of the key factors influencing students’ mathematical representation skills.